Conoscopic image of a biaxial negative in a reentrant discotic – biaxial nematic phase transition. Issue 7 (28th May 2021) - Luders, D.D.; Arcolezi, G.M.; Pereira, M.L.G.; Braga, W.S.; Santos, O.R.; Simões, M.; Kimura, N.M.; Sampaio, A.R.; Palangana, A.J
ABSTRACT: Conoscopic images have confirmed the occurrence of biaxial positive ( N B + ) and biaxial negative ( N B − ) nematic phases between the two uniaxial nematic (discotic – N D and calamitic – N C ) phases. Biaxial positive ( N B + ) nematic phase was also optically characterised between two uniaxial N D phases. These nematic phases are found in different phase diagram lines of potassium laurate ( K L ), decanol ( D e O H ) and deuterium oxide ( D 2 O ) lyotropic mixtures. In limited concentration range between the two phase diagram lines the following phase sequence ( N D → N B + → N B − → N B + → N D ) is determined here through conoscopic images. An analysis of the meaning of this result leads us to conclude that the biaxial nematic phase range between uniaxial nematic phases of phase diagrams with nematic lyotropic materials is separated in two regions: one has an optically positive signal and the other, having an optical negative signal. Graphical abstract: